Value-added offer on Spanich Websites from Translation and Language Service Providers - Luna García, Rosa (2022)
The main objective of this empirical applied and documental study was to identify value-added services offered on web pages of translation service providers and language service providers in Spanish language speaking countries. The sample of this study comprised 169 web pages of translation service providers and language service providers. The analysis was made using the contents analysis technique, while data coding/tabulation was made using the SPSS software. The research arrived at the following general conclusions: 1. Both translation service providers and language service providers offer value-added services related to seven types of management:  language, editorial, translation, audiovisual translation, contents, events, and computer-assisted  translation; the services with the greatest offer are audiovisual translation management and language management; 2. Companies are the suppliers offering the highest number and diversity of value-added services; and 3. The countries with the largest offer of value-added services in the Spanish speaking world, in rank order, are Spain, Colombia and Peru.